Bottomstress in the Baltic Proper 1999-2000 - Jönsson, Anette (SMHI - Swedish Meteorological and Hydrological Institute, 2019)
Calculations of bottom friction velocity due to waves for five different particle sizes. Wave data are modelled with HYPAS, a second generation spectral wave model (Günther, Rosenthal, 1995). HYPAS is forced by MESAN (Häggmark et al. 2000). Ice is not included in the calculation. Used equations can be found in Danielsson et al (2007) Resuspension patterns in the Baltic Proper. Journal of Sea Research, 57, 257-269.

Notes: HYPAS wave model is used for wave data. SMHI set up is used and it is forced by MESAN data. The modelled winds are known to be slightly underestimated why the wave field might be the same. Ice is not included, which gives that the waves are exagerrated in times when there are ice.

The dataset variables are:
Um - maximum orbital velocity at the bottom
Us006 - is the Shields parameter (non-dimensionalized bottom stress) for grain size diameter 0.06 mm
Us025 - Shields parameter for grain size diameter 0.25 mm
Us050 - Shields parameter for grain size diameter 0.50 mm
Us100 - Shields parameter for grain size diameter 1.00 mm
Us200 - Shields parameter for grain size diameter 2.00 mm

The Shields parameter used is presented in Eq 6 in Jönsson, A (2006) A model study of suspended sand due to surface waves during a storm in the Baltic Proper, Journal of Marine Systems, 6391-104.

Beräkningar av bottenfriktionshastighet på grund av vågor för fem olika partikelstorlekar. Vågdata har modellerats med HYPAS, en spektralvågsmodell (Günther, Rosenthal, 1995).

Se engelska katalogsidan för utförligare beskrivning: https://snd.gu.se/en/catalogue/study/ECDS0100
Bottenstress i Östersjön 1999-2000
Keywords: OCEAN WAVES; oceanography; oceanografi; Sea regions; Havsområden; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav